Long Term Outcome and Immune Function After Hematopoietic Stem Cell Transplantation for Primary Immunodeficiency - Gennery, Andrew R.; Lankester, Arjan; , Inborn Errors Working Party (IEWP) of the European Society for Blood; Marrow Transplantation (EBMT) (Frontiers in Pediatrics, 2019)
Transplantation techniques for patients with primary immunodeficiencies have improved so that survival from the procedure in many cases is around 90%. However, long term complications may arise as a result of the use of conditioning agents or not, resulting in variable immune reconstitution, the long term effects of chemotherapy, particularly on fertility, and complications relating to the genetic disorder, unresolved by transplantation. For patients with severe combined immunodeficiency (SCID), long term T- and B-lymphocyte immune reconstitution is best achieved after pre-transplant chemotherapy. For patients who receive an unconditioned infusion of donor stem cells, the quality of immune reconstitution depends on the SCID genotype. Long term effects include chemotherapy-induced impaired fertility, and sequelae specific to the genotype. For patients with other primary immunodeficiencies, conditioning is required – sequelae related to direct effects of chemotherapy may be observed. Additional long term effects may be observed due to partial donor chimerism resulting in incomplete eradication of disease, and other geno-specific effects.